Impact of diet on vitamin D status in a Sri Lanka-based sample of pregnant women - Kaneshapillai Anusha; Liyanage Guwani; Hettiaratchi Usha; Gunasekera Dulanie (Journal of Health and Social Sciences)
Introduction: Vitamin D deficiency is common during pregnancy in Asian countries. However, there is little knowledge about vitamin D status of pregnant mothers and, therefore, supplements are not routinely provided in public clinics and government hospitals in Sri Lanka. Therefore, aim of this study was to assess vitamin D status and adequacy of vitamin D intake in a sample of pregnant mothers. Methods: This was a secondary analysis of existing data from a prospective cohort study. A convenience sample of 89 healthy and non-vitamin D supplemented Sri Lanka-based pregnant mothers was recruited during the third trimester of their pregnancy. Dietary vitamin D intake was assessed through a food frequency questionnaire, while serum was analysed for vitamin D, parathyroid hormone (PTH) and other markers of bone biochemistry. Results: In our sample, average daily dietary intake of vitamin D was 1,289.4 ± 1,225.6 IU/day (range: 56 - 5400 IU). A significant proportion of mothers (45%) consumed < 600 IU of vitamin D per day. More than half of our sample (56.9%) received vitamin D though fortified milk powder and 36% from fish consumption. Most of mothers (69%) consumed small fish and none of them received vitamin D supplementation. There was a significant positive correlation between dietary vitamin D and serum 25-hydroxyvitamin D (25(OH)D) (r = 0.355, P < 0.01). 12.4%, 50.6% and 37% of the mothers were vitamin D deficient, insufficient and sufficient, respectively. We showed a significant difference in levels of dietary vitamin D intake between serum 25(OH)D deficient/insufficient (dietary vitamin D: 1,083.6 ± 1,026.4 IU/day) and 25(OH)D sufficient (dietary vitamin D: 1,638.5 ± 1,456.1 IU/day) groups. Discussion and Conclusion: Dietary intake of vitamin D was inadequate in Sri Lankan non-vitamin D supplemented mothers. Further evaluation of vitamin D status and requirement for supplementation in a nationally representative sample is essential.